Influence of various factors on surface properties of elastomeric materials based on nitrile butadiene rubbers - О. А. Dulina; Е. V. Eskova; А. D. Tarasenko; S. V. Kotova (Тонкие химические технологии, 2022)
Objectives. The influence of the technological additive content and accelerated aging conditions on the surface energy and elastic-strength properties of nitrile butadiene rubbers with an average acrylic acid nitrile content and rubbers based on them were studied in the paper.Methods. The free surface energy of the samples was determined under the standard conditions and in the accelerated aging conditions with the use of the Owens, Wendt, Rabel, and Kaelble method.Results. It was shown that the elastomeric materials surface energy is influenced by surfactants such as rosin and stearic acid, which are typical ingredients of rubber compounds. It was also found that the thermal aging effect on the physical and mechanical properties of rubbers based on nitrile butadiene rubbers depends on the method of rubber isolation from latex and on the nature of the surfactant components in the samples.Conclusions. The analysis of the results obtained shows that the change in the vulcanizates physical and mechanical properties, depending on the technological additive content and the temperature effect, occurs along with a change in the critical surface tension.